The Concept of Moral Landscapes and its Applicability for Theory Formation and Empirical Studies on Teaching in the Geography Classroom - Applis, Stefan (Journal of Geography Education, 2018)
’Moral landscapes’ is a new concept being used in Sociology, Philosophy and Political Science. Its central implications are linked strongly with questions of value based learning and Intercultural learning in the classroom. This paper discusses its applicability for reflecting teaching and learning arrangements in the Geography classroom and examines its connections to latest research findings in American Psychology. This shall be supplemented by findings from a qualitative-reconstructive study with teacher trainng students that show narrow limits of developing moral and intercultural judgment in the Geography classroom.